1966
DOI: 10.2307/3895721
|View full text |Cite
|
Sign up to set email alerts
|

Using Growing-Season Precipitation to Predict Crested Wheatgrass Yields

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…The season of clipping had no effect on any variable, despite published reports of seasonal variation in carbohydrate and nitrogen reserves of grasses such as A. cristatum (Trlica & Cook 1972;Miller et al 1990;de Kroon & Bobbink 1997). A 10-year experiment in Colorado found that the season of heavy grazing had no effect on forage yield (Currie & Peterson 1966), consistent with our results. Further, A. cristatum persisted after 20 years of annual heavy spring grazing near our study site (Hubbard 1949), even though grazing occurred near the trough of carbohydrate reserves when it should be most deleterious.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The season of clipping had no effect on any variable, despite published reports of seasonal variation in carbohydrate and nitrogen reserves of grasses such as A. cristatum (Trlica & Cook 1972;Miller et al 1990;de Kroon & Bobbink 1997). A 10-year experiment in Colorado found that the season of heavy grazing had no effect on forage yield (Currie & Peterson 1966), consistent with our results. Further, A. cristatum persisted after 20 years of annual heavy spring grazing near our study site (Hubbard 1949), even though grazing occurred near the trough of carbohydrate reserves when it should be most deleterious.…”
Section: Discussionsupporting
confidence: 91%
“…Among‐year variation in A. cristatum cover in control plots is related to growing‐season rainfall. Because A. cristatum is least abundant in dry years (Currie & Peterson 1966; Curtin et al 2000; Bakker et al 2002), control efforts might be most successful in dry years. The only reported failures of established stands of A. cristatum (10–17 year old) occurred in arid areas of Utah and Nevada and were attributed to drought (Bleak et al 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Observations during the study years indicated that differences in characteristics of storms at the watershed and at head- quarters were negligible. Also, results of range research on pastures located near the study area (Currie and Peterson 1966), indicate that differences in rainfall were minor. Measurements of gully peak flows are approximate.…”
Section: Study Methodsmentioning
confidence: 92%
“…Therefore, for forage crops, yield prediction research that could be helpful for cultivation management and forage production arrangement is very necessary. Currie and Peterson (1966) used a stepwise regression to predict crested wheatgrass yields using growing-season precipitation in Colorado, USA. Generally, the statistical models are constructed based on long term crop yield records and several climatic variables such as temperature and precipitation (Thompson 1969;Basso et al 2013).…”
Section: Introductionmentioning
confidence: 99%